Genetic Uniqueness and Genetic Structure of Populations of Picea obovata Ledeb. and Larix sibirica Ledeb. in the Northern and Middle Urals - Zhulanov, Andrei; Chertov, Nikita; Nechaeva, Yulia; Pechenkina, Viktoriia; Zhulanova, Larisa; Boronnikova, Svetlana; Kalendar, Ruslan (Forests, 2023)
Establishing sustainable plantations with genetic diversity equivalent to that of natural populations is vital for successful reforestation efforts. In this study, we present an innovative approach for selecting populations suitable for reforestation, taking into account their genetic uniqueness using Inter Simple Sequence Repeats (ISSR) markers. Our investigation focused on six populations of Picea obovata Ledeb and six populations of Larix sibirica Ledeb, collected from the Northern and Middle Urals. We found that the indicators of genetic diversity were significantly higher in L. sibirica compared to P. obovata, while the number of rare alleles was greater in Siberian spruce (R = 19). Among the P. obovata populations, the Cherdyn’s forestry exhibited notably high genetic diversity, and for L. sibirica, the Gainy’s forestry stood out in this regard. Moreover, the genetic subdivision of the six P. obovata populations (GST = 0.331) was higher than that of the six L. sibirica populations (GST = 0.177). To ensure optimal seed selection considering the genetic originality coefficient (GOC) and population differentiation, we recommend utilizing the P. obovata population from Gainy’s forestry with a GOC of 0.554 and the L. sibirica population from Cherdyn’s forestry with a GOC of 0.372. These populations harbor typical alleles characteristic of the research region, making them ideal candidates for seed selection. Furthermore, the specific alleles identified can serve as valuable markers for determining the geographic origin of P. obovata and L. sibirica wood, aiding in efforts to trace the sources of these species in forestry and trade practices.